Percepción De Los Estudiantes De Odontología De La Uan, Sede Armenia, Frente A Pacientes Con Vih/Sida (2021)
The human immunodeficiency virus (HIV) has generated a pandemic that has coexisted with us for approximately four decades. Quindío is one of the Colombian departments with the highest HIV incidence rate, with 58 positive cases per 100,000 inhabitants in 2020. Its lack of curability and transmission routes have triggered stigmatization and discrimination. This generates more concern when the stigma or discrimination comes from health professionals, because it could cause the denial of access to basic services.